Interaction of atenolol and adrenaline with respect to intraocular pressure. - Rushton, A (1979)
1. The effects of topically administered atenolol 4% and adrenaline 1% on intraocular pressure (IOP) were investigated in fourteen healthy male human volunteers. Both the sole and combined effects of single doses of the formulations were recorded over a 7 h period. 2. Adrenaline and atenolol both produced significant reductions in IOP when compared to the placebo control, although the pattern of response differed. 3. Adrenaline had a rapid onset of action, resulting in a significant pressure reduction by 45 min post drug administration. A small upswing in IOP then occurred between 45 and 90 min, followed by a prolonged secondary reduction phase. 4. Atenolol produced a gradual reduction in IOP which reached a maximum at 180 min post drug administration and subsequently declined between 300 and 420 min. 5. Combined treatment with atenolol and adrenaline resulted in additive effects up to 180 min, and the early pressure upswing recorded with adrenaline was completely abolished. 6. The results are compatible with the hypothesis that beta 1-adrenoceptor stimulation elevates intraocular pressure. The correlation of these results with relevant animal and human pharmacological data is discussed.